Engaging Prospective Elementary Teachers in Lesson Study. Issue 5 (28th May 2018) - Appova, Aina K.
Abstract: This paper discusses the ways in which teacher educators can effectively engage prospective teachers (PTs) in lesson study during mathematics methods courses. Evidence from this work suggests that engagement in lesson study provides PTs with opportunities to strengthen their knowledge about mathematics, students, and pedagogy. More specifically, the results demonstrated that lesson study helped PTs to engage in deep and thoughtful discussions about mathematics, reflect on their teaching, and make effective changes to their lessons that showed noticeable improvements in student learning. Recommendations from this work provide specific methods-course suggestions on the implementation of lesson study as a model for PTs' professional and practitioner development, including strategies and guiding questions that teacher educators can utilize to help deepen PTs' knowledge about mathematics, teaching, and student learning.